Diversifying Chile's climate action away from industrial plantations - Hoyos-Santillan, Jorge; Miranda, Alejandro; Lara, Antonio; Sepulveda-Jauregui, Armando; Zamorano-Elgueta, Carlos; Gomez-Gonzalez, Susana; Vasquez-Lavin, Felipe; Garreaud, Rene D.; Rojas, Maisa (My University, 2021)
As president of the Climate Change Conference of the Parties, Chile has advocated for developing ambitious commitments to mitigate greenhouse gas emissions to achieve carbon-neutrality by 2050. However, Chile's motivations and ambitious push to reach carbon-neutrality are complicated by a backdrop of severe drought, climate change impacts (i.e., wildfires, tree mortality), and the use of industrial plantations as a mitigation strategy. This has become more evident as widespread and severe wildfires have impacted large areas of industrial plantations, transforming the land-use, land-use change, and forestry sector from a carbon sink to a net carbon source. Consequently, Chile must diversify its climate actions to achieve carbon-neutrality. Nature-based solutions, including wetlands-peatlands and oceans, represent alternative climate actions that can be implemented to tackle greenhouse gas emissions at a national level. Diversification, however, must guarantee Chile's long-term carbon sequestration capacity without compromising the ecological functionality of biodiverse treeless habitats and native forest ecosystems.
Keywords: climate action; wildfires; nature-based solutions; native forest; carbon neutrality; net-zero